Manajemen Sebagai Sains, Seni dan Profesi serta Implementasinya di Madrasah Tsanawiyah Madinatun Najah Rengat - As'adut Tabi'in; Kemas Imron Rosadi; Muntholib Muntholib (STAIN Bengkalis, 2021)
Management is a systematic and structured effort to make adjustments between planning, organizing, actuating, controlling, and evaluating so that their main goals are achieved. This research was conducted in Madrasah Tsanawiyah at the Yayasan Pendidikan Agama Islam Rengat (YPAIR) which was established and inaugurated by the Japanese government in April 1945. This article aims to describe the implementation of management in the Madrasah. The method used is qualitative research with an analytical descriptive approach. Data were collected through observation, interviews, and documentation. The conclusion of this article shows some facts that the leadership of the head of Madrasah from the beginning until now, tends to apply the concept of management as an art. Because, it was not found from several changes to the head of the madrasa, as a professional or having taken management-related education. The change in the leadership of the head of the Madrasah was chosen on the basis of kinship, which then affects the quality of Madrasah management and the achievement of goals.